THE MEANING OF LUQMANUL HAKIM'S WILL IN SURAH LUQMAN VERSES 13-19 - Hanif Maulana (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research examines the meaning of Luqmanul Hakim's will in SurahLuqman verses 13-19. The research method used in this research is a qualitative method with a content analysis approach. The data collection technique used by the author in this article is to translate verses from the Al-Qur'an, interpret andconclude the understanding that researchers have sought from these verses, so as to obtain results that are more detailed and clear and can be understood easily by everyone. reader. There are several values of Islamic educationcontained in the Al-Qur'an Surah Luqman verses 13-19, basically covering three fundamental education, namely; aqidah education, moral education, and sharia education. The aqidah education contained in Luqman's letter is in verse 13, namely